2018
DOI: 10.1242/jcs.216986
|View full text |Cite
|
Sign up to set email alerts
|

The budding yeast Pex5p receptor directs Fox2p and Cta1p into peroxisomes via its N-terminal region near the FxxxW domain

Abstract: The import of most of peroxisomal proteins into the lumen of their target organelle is driven by C-terminal (PTS1) or N-terminal (PTS2) signals recognized by the Pex5p or Pex7p receptors, respectively. However, some proteins in budding yeast, such as acyl-CoA oxidase (AOx) and carnitine acetyltransferase (Cat2p), are imported into peroxisomes via an alternative route that does not rely on known PTS signals and involves the Pex5p receptor N-terminal region. Here, we show that two other budding yeast peroxisomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 52 publications
1
25
0
Order By: Relevance
“…We 230 propose that the location of cytosolically-synthesised CAT is determined by competition 231 among different potential-binding partners as a consequence of reduced import into 232 peroxisomes and/or increased retention of CAT in the cytosol. While sensitivity of 233 peroxisomal protein import to redox status is likely to impact import of all peroxisome 234 proteins, CATALASE which has a non-canonical targeting signal (Mhamdi et al, 2012) 235 (Rymer et al, 2018) may be more sensitive and indeed PEX5, the major peroxisome import 236 receptor, has been proposed to specifically retain mammalian catalase in the cytosol under 237 conditions of oxidative stress (Walton et al, 2017). This property, combined with the 238 potential to interact with an array of cytosolic proteins as shown in Figure 2 could allow 239 swift control of catalase localisation between compartments in such a way as to influence 240 various redox signalling pathways.…”
Section: Candidates As a Paradigm For Redox Regulated Movement In Plamentioning
confidence: 99%
“…We 230 propose that the location of cytosolically-synthesised CAT is determined by competition 231 among different potential-binding partners as a consequence of reduced import into 232 peroxisomes and/or increased retention of CAT in the cytosol. While sensitivity of 233 peroxisomal protein import to redox status is likely to impact import of all peroxisome 234 proteins, CATALASE which has a non-canonical targeting signal (Mhamdi et al, 2012) 235 (Rymer et al, 2018) may be more sensitive and indeed PEX5, the major peroxisome import 236 receptor, has been proposed to specifically retain mammalian catalase in the cytosol under 237 conditions of oxidative stress (Walton et al, 2017). This property, combined with the 238 potential to interact with an array of cytosolic proteins as shown in Figure 2 could allow 239 swift control of catalase localisation between compartments in such a way as to influence 240 various redox signalling pathways.…”
Section: Candidates As a Paradigm For Redox Regulated Movement In Plamentioning
confidence: 99%
“…Interestingly, the N-terminal half of Pex5p is also important for the recognition and peroxisomal import of carnitine acetyltransferase (Cat2p), which possesses a functional PTS1 signal in the C-terminus that can be abrogated without noticeable consequences to localization of this protein (Klein et al, 2002). Moreover, we recently demonstrated that two other peroxisomal proteins, (1) the multifunctional enzyme of the peroxisomal fatty acid beta-oxidation pathway that comprises the 3-hydroxyacyl-CoA dehydrogenase and enoyl-CoA hydratase (Fox2p) and (2) the peroxisomal catalase A, both containing the PTS1 signals at their C-termini, are also partially dependent on this side branch of the Pex5p-dependent import route (Rymer et al, 2018). It remains an open question whether the list of S. cerevisiae proteins interacting with the N-terminal half of the Pex5p en route to peroxisomes is complete.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it is in this region that reside all the necessary and sufficient domains required for the interaction of PEX5 with the DTM, recognition and import of PTS2 proteins (in the large isoform of PEX5 only), monoubiquitination of PEX5 and its export by the receptor export module (REM) [41,42,47,66,67,76,77]. In addition, there are also several data suggesting that this domain interacts with several PTS1 proteins [78][79][80][81][82][83] although the main binding site for this type of cargo proteins resides in the C-terminal half of PEX5 (see below).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of them are the so-called pentapeptide motifs [66,67,88]. These SLiMs are best known as mediators of interactions with two DTM components, PEX13 and PEX14 [65][66][67][70][71][72][73], but some of them may also modulate or even participate in interactions with PTS1 proteins [78,79,82,83]. Another domain present in the N-terminal half of PEX5 was structurally characterized in the yeast PEX5-like protein PEX21 and shown to interact with both the PTS2 sequence and PEX7 [41,89].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation